2020
DOI: 10.3390/su12208706
|View full text |Cite
|
Sign up to set email alerts
|

Improving Mechanical Textile Recycling by Lubricant Pre-Treatment to Mitigate Length Loss of Fibers

Abstract: Although there has been some research on how to use short fibers from mechanically recycled textiles, little is known about how to preserve the length of recycled fibers, and thus maintain their properties. The aim of this study is to investigate whether a pre-treatment with lubricant could mitigate fiber length reduction from tearing. This could facilitate the spinning of a 100% recycled yarn. Additionally, this study set out to develop a new test method to assess the effect of lubricant loading. Inter-fiber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…Mechanical recycling is one of the main methods to recycle pre-consumer cotton textile waste [6]. The shredding and tearing process in the mechanical recycling shortens the fiber length and reduces fiber quality, so it is a downcycling process to produce low-value products such as rags or insulation materials [32], or the mechanically recycled textiles need to be blended with a high percentage of new fibers in high-quality fabric production [6]. This research explored different mechanical recycling methods to recycle post-consumer cotton waste and developed high-value products including bags, a hat, garments, cell phone and glasses cases, and decorative textiles from the recycled materials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical recycling is one of the main methods to recycle pre-consumer cotton textile waste [6]. The shredding and tearing process in the mechanical recycling shortens the fiber length and reduces fiber quality, so it is a downcycling process to produce low-value products such as rags or insulation materials [32], or the mechanically recycled textiles need to be blended with a high percentage of new fibers in high-quality fabric production [6]. This research explored different mechanical recycling methods to recycle post-consumer cotton waste and developed high-value products including bags, a hat, garments, cell phone and glasses cases, and decorative textiles from the recycled materials.…”
Section: Discussionmentioning
confidence: 99%
“…Apparel brands such as Patagonia, Swany America, and Quiksilver in France are members of Teijin's "eco circle" program and develop products using Teijin's chemically recycled Eco Circle TM polyester fibers [31]. The shredding and tearing processes in the mechanical recycling shorten the fiber length and reduce fiber quality, which may result in low value products such as rags or insulation materials [32], or the blending of mechanically recycled materials with a high percentage of new materials in fabric production to assure fabric quality [6].…”
Section: Products Made From Recycled Textilesmentioning
confidence: 99%
“…This treatment showed to be successful in reducing the loss of fiber length, decreasing inter-fiber cohesion, and facilitating the tearing process. The authors showed that it was possible to rotor-spin 100% of mechanically fractionated fibers after this treatment [43].…”
Section: Mechanical Fractionation And/or Separationmentioning
confidence: 99%
“…An additional problem is that recycled wool fibers are generally of lower quality than virgin wool fibers, mainly due to the shortening of fiber lengths [18]. It can be necessary to mix short fibers with virgin fibers to enable respinning into yarns and achieve the required quality [24][25][26]. The Circular Footprint Formula's (CFF, [27]) attempts to capture this aspect in environmental analyses of textiles could be applied as has been discussed in detail in Wiedemann et al [16].…”
Section: Introductionmentioning
confidence: 99%